Odpowiedź :
Odpowiedź:
w(x) = [tex]x^5 - x^3 + x^2 - 1[/tex]
w(x) = P(x)*( x -1 )*(x + 1)*( x+ 2) + a x² + b x + c
Dla x = 1 Mamy W(x) = 1 - 1 + 1 - 1 = a + b + c
Dla x = - 1 Mamy W(x) = -1 + 1 + 1 - 1 = a - b + c
Dla x = - 2 Mamy W(x) = -32 + 8 + 4 - 1 = 4 a -2 b + c
Mamy układ równań
1) a + b + c = 0
2) a - b + c = 0
3) 4 a -2 b + c = - 21
--------------------
Odejmujemy 1) - 2) 2 b = 0
b = 0
---------
Z 2) c = - a
Wstawiam do 3) 4 a - 0 - a = - 21
3 a = - 21 / : 3
a = - 7
c = - (-7) = 7
więc R(x) = - 7 [tex]x^2 + 7[/tex]
==================
Szczegółowe wyjaśnienie: